Ubiquitin-mediated degradation restricts spatiotemporal accumulation of the cytoplasmic male sterility protein WA352 to anthers in rice - Zixu Zhang; Zhi Ding; Xueye Feng; Jingjing Huang; Xu Peng; Yubin Xiao; Wubei Zong; Zhe Zhao; Yao-Guang Liu; Yongyao Xie; Letian Chen (Proceedings of the National Academy of Sciences, 2025)
Cytoplasmic male sterility (CMS) is caused by mitochondrial genes that are constitutively expressed in plant tissues, although the encoded proteins preferentially accumulate in anthers. The mechanisms regulating CMS protein accumulation remain unclear. Here, we explored this process using wild-abortive CMS (CMS-WA) rice ( Oryza sativa ). We show that WA352, the causal protein of CMS-WA, is degraded by the ubiquitin–proteasome system (UPS). Structural analysis and protein truncation assays revealed that the N terminus of WA352 is critical for its anchoring to the inner mitochondrial membrane and its UPS-mediated degradation. Functional complementation confirmed that WA352 151–352 , lacking the N-terminal domain, accumulates constitutively in vegetative tissues, causing a reactive oxygen species burst and retarding rice growth. We further identified three mitochondrion-localized F-box proteins that participate in WA352 ubiquitination and degradation. Our findings demonstrate that UPS-mediated regulation restricts WA352 accumulation to anthers, allowing it to specifically disrupt anther development, thus helping to explain the male-specific effects of CMS genes in plants.